Characterization of Pd-Cu/gamma-Al2O3 catalysts by XPS and catalytic measurements - Batista, Jurka (Kovine zlitine tehnologije, 1998)
Liquid-proces hydrogenaation using a solid catalyst provides a potential technique for the removal of nitrates from waters. Various Pd-Cu bimetallic catalysts were prepared according to different impregnation sequences of ?$γ-Al_2O_3$? support, and tested for the selective hydrogenation of aqueous nitrate solutions to nitrogen. Measurements were performed in a semi-batch slurry reactor at T=293 K. The results show that the nitrate-to-nitrate reduction step undergoes a structure-insensitive hydrogenation with a heterolytic electron transfer. The most suitable distribution of metallic copper and palladium phases, which results in the minimum formation of ammonium ions, was obtained for the catalyst preparation procedures, in which the alumina is impregnated first by copper salt. XPS examination of mono- and bimetallic catalysts revealed that in all examined samples Pd is present in the metallic form. On the other hand, in a Cu/?$γ-Al_2O_3$? sample previously reduced at T=773 K in hydrogen atmosphere, copper is found in +1 and +2 oxidation states. In the presence of both elements on the catalyst surface, copper is detected in low oxidation states (i.e., 0 and +1).
Keywords: katalizatorji; paladij; baker; aluminijev oksid; hidrogeniranje; kemijska kinetika